IT Governance Priorities using COBIT 2019 Design Factors for the STIE AMA Academic Information System - Gabriela Winanti; Evi Maria (SISTEMASI, 2026)
The Academic Information System (SIAKAD) is a core service that supports higher education operations and requires effective information technology (IT) governance to ensure regulatory compliance, data quality, risk management, and service continuity. This study aims to identify IT governance priorities for the STIE AMA Salatiga Academic Information System using the COBIT 2019 Design Factors before conducting a capability assessment. A qualitative research approach was employed, utilizing a structured COBIT 2019 assessment based on observations, interviews, and Design Factors questionnaires. The analysis evaluated the ten COBIT 2019 Design Factors to determine the importance scores of the 40 governance and management objectives. The results indicate that service stability orientation, regulatory compliance, risk management, and dependence on cloud/SaaS services collectively define eight priority objectives: MEA03, EDM03, APO12, APO14, DSS05, DSS02, APO08, and DSS04. The findings further reveal that, within a cloud/SaaS environment, IT governance priorities primarily focus on regulatory compliance, risk management, data governance, service security, external service provider management, and service continuity. The study demonstrates that the COBIT 2019 Design Factors provide an effective mechanism for identifying relevant governance and management objectives prior to capability assessment, thereby establishing a structured basis for prioritizing IT governance evaluation and improvement in accordance with organizational characteristics.